Enrichment of low-frequency functional variants revealed by whole-genome sequencing of multiple isolated European populations - Yali Xue (Nature Portfolio, 2017)
Isolated populations often have special genetic compositions that can be leveraged for genetic association studies. Here, Xue and colleagues generate and analyse 3,059 low-depth whole-genome sequences from eight European isolated populations and two matched general populations.